Feasibility of the Qiblah Craft Mukena Business at Cikarang Festival: Opportunities and Challenges - Fitriyani, Yuli; Sari, Tiara Permata; Nuraini, Desiana Indah; Aprillianti, Fitria Wulan; Hidayah, Moh Rony; Andriana N, Rifqi (Review: Journal of Multidisciplinary in Social Sciences, 2025)
A feasibility study of the mukena business at the Cikarang Festival (Cifest) shows promising market potential, along with the growing population and industrial sector in the area. With a predominantly Muslim population and a growing demand for practical, high-quality products, the mukena business has potential for growth. Financial analysis indicates positive profit prospects, but challenges such as intense competition, economic fluctuations, and the need to meet diverse design preferences are factors that need to be considered. Overall, with the right marketing strategy and efficient management, the mukena business at the Cikarang Festival (Cifest) can be considered feasible and has the potential for long-term growth.